Political Leadership Policy and Education in PSIAFIL Perspective at Pasim National University - Endri Hendrayana; Sugeng Djatmiko; Ishak Abdulhak; Achmad Mudrikah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study is to determine the political policy of educational leadership at the National University of Pasim in terms of Psychology, Sociology, Religion and Philosophy (PSIAFIL). the research used was quantitative with a descriptive approach. The data used is primary data through the distribution of questionnaires. The research population is structural officials, lecturers and education staff at the National University of Pasim, while the sample used is 60 respondents (Slovin Formula). The sampling used is probability sampling with the type of Proportionate Stratified Random Sampling. The instrument test uses validity and reliability tests. The data analysis technique used descriptive statistical analysis through frequency distribution (SPSS). The results of the study stated that the political conditions, policies and educational leadership at the National University of Pasim were in the good category. However, there are aspects that need further attention, namely in terms of decision control, aspects of participation and in terms of coordination. From a psychological point of view, leadership that occurs is more inclined to leaders with phlegmatic personality types. Then from a sociological point of view, leadership today has a high level of concern and can keep up with the times. Likewise, from a religious point of view, the current leader is more wise, and sympathetic, both in politics and in every policy. In the point of view of the current leadership philosophy is more wise and fair.